Questioning the univocity ideal. The difference between socio-cognitive Terminology and traditional Terminology - Temmerman, Rita (HERMES - Journal of Language and Communication in Business, 2017)
In this article we are questioning the univocity ideal of traditional Terminology. We show how traditional Terminology in line with Saussurian structuralism ignores part of the interplay between the elements of the semantic triangle. Cognitive semantics and functional linguistics have offered an alternative for the Saussurian structuralist approach. Several of their findings can be of use for the development of socio-cognitive Terminology. In the LSP of the life sciences, the structure of concepts reflects their episte-mological function. This could have consequences for the principles and methods of terminological description. While some concepts (like intron ) are clear-cut and can therefore be submitted to the principle of univocity, others (like blotting and biotech-nology) have prototype structure. For prototypically structured categories univocity can not be the aim as polysemy, synonymy and figurative language are part of their naming history.